2004
DOI: 10.1002/ange.200460271
|View full text |Cite
|
Sign up to set email alerts
|

Forced Peptide Synthesis in Nanoscale Confinement under Elastomeric Stamps

Abstract: In solution, only collisions between molecules of sufficient energy to overcome the activation barrier lead to the formation of reaction products. The rate of the reaction is influenced by the temperature, concentration of the reactants, solvent, orientation of the reactants, and structure of the molecules. Catalysts or enzymes lower the activation energy by making available alternative reaction pathways and preorganize the reactant molecules in close proximity, which leads to an increase in the effective conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…[14] Recently, Huck and co-workers [15] proposed the application of mCP for the in situ synthesis of oligopeptides exclusively in the contact areas between substrate and the poly-(dimethylsiloxane) (PDMS) stamp. The advantage of covalent mCP of peptides is that a chemical bond is formed between the protein and the substrate SAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Recently, Huck and co-workers [15] proposed the application of mCP for the in situ synthesis of oligopeptides exclusively in the contact areas between substrate and the poly-(dimethylsiloxane) (PDMS) stamp. The advantage of covalent mCP of peptides is that a chemical bond is formed between the protein and the substrate SAM.…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IRRAS spectra of SAM 3 (obtained by 1 h of chemisorption of col3a1 from solution) and SAM 3* (obtained by 15 min of mCP with a flat, featureless stamp) are virtually identical, once more confirming the remarkable efficiency of the immobilization reaction in the confinement between stamp and substrate. [15,20] However, the amine band is shifted to higher wavenumbers and also the ratios of amide I to amide II are not equal for SAM 3 and SAM 3*, which could indicate differences in hydration and orientation of the protein layers.…”
mentioning
confidence: 99%
“…The results suggested that such nanomemory system can operate at a density of no less than 10 11 bits/cm 2 . To solve the problem of double junctions, the molecule of interest can be controllably deposited onto the desired locations of the nanowire/tube using techniques such as dip-pen nanolithography and stamp-printing method [90,91]. D. Etching hole plus nanotube and Nanopore molecular junctions A silicon/molecule/nanotube approach has been developed as a testbed for fabrication of metalfree molecular junctions, i.e., etching hole plus nanotube method [52].…”
Section: Photoresist Patterns Processmentioning
confidence: 99%
“…These studies were mostly focused on the synthesis, organization/immobilization, modification, and simple characterization of the biomaterials [148]. Although, it was realized to controllably deposit molecules of interest to desired locations on substrate using AFM based dippen nanolithography [90] and/or stamp printing methods [91]. Electrical properties of single biomaterial were measured using CAFM or STM in combination with nanoparticles [151].…”
Section: Bioelectronicsmentioning
confidence: 99%
“…Whether this is sufficient to explain the formation of highly ordered SAMs is not clear, as there are no detailed studies of SAM formation in neat alkanethiols. Intriguingly though, chemical reactions leading to new covalent bonds between SAM end groups and molecules printed on top using μCP also seem to proceed much faster and without requiring activated functional groups or catalysts 20. 21 The formation of amide bonds between amine‐terminated SAMs and carboxylic acid “inks” seems to proceed without the need for activated esters or catalysts, and the effect is only observed when the “inks” are pressed onto the surface using PDMS stamps 20.…”
mentioning
confidence: 99%